Treatment of synthetic textile effluent by electrocoagulation using aluminum and iron electrodes (Research, Society and Development, 2022)
As an alternative to conventional water treatments, electrocoagulation (EC) is an electrochemical process based on the production of a coagulating agent in situ through anodic oxidation. The objective of this article is to evaluate the influence of different parameters in the EC process for the treatment of a synthetic textile effluent containing methylene blue, such as applied electrical potential, electrolysis time, initial and final pH of the effluent and the type of electrode used. (Iron and Aluminium). The dye removal rate was monitored by ultraviolet-visible (UV-vis) spectroscopy. The results obtained showed greater efficiency with increasing electrical potential and electrolysis time, since the amount of coagulating agents formed is proportional to these two parameters. However, a maximum time of 60 minutes was used, since removal rates did not increase significantly with longer times. The Iron electrode proved to be more efficient with a dye removal rate of 96.7%, while the Aluminum electrode was more eficiente with an 84.4% one. The influence of the pH shows that the acid medium presented better results in high electrical potential. The analysis of the mass consumed in the electrodes indicated that the aluminum electrode suffered greater mass loss and this is due to intrinsic characteristics of the metal. At maximum efficiency of the EC process, energy consumption of 15.3 kWh/m3, and 22.7 kWh/m3 were verified for the Iron, and the Aluminum electrodes, respectively. These results show that the Iron electrode is preferable, either in terms of removal efficiency or economic viability.